Diversification in euro area stock markets: country versus industry - Gerard Moerman (European Central Bank (ECB), 2004)
The harmonisation of fiscal and economic policy within the European Monetary Union (EMU) has had a considerable impact on the economies of member countries in the past decade. In particular, several studies indicate that the proceeding economic integration among euro area countries has important consequences for the factors driving asset returns in financial markets. This study concentrates on the implications of the changing structure of security returns for asset management. Using recent euro area stock markets data, we find clear evidence that diversification over industries yields more efficient portfolios than diversification over countries. We show that this result is robust with respect to the information technology-hype and different volatility regimes. This contrasts with e.g. Rouwenhorst (1999), who finds, based on a different methodology and a different sample period, that country diversification strategies are superior. We regard this paper as a robustness check challenging the existing strand of literature and show that Rouwenhorst's (1999) conclusions seem to be outdated.
Keywords: G11; G15; 330; country; EMU; euro area stock markets; industry factors; portfolio diversification